CLASSIFICATION OF “SET OF COMPETENCIES” IN THE CONTENT OF VOCATIONAL EDUCATION - Kholmukhamedov Murodullo Makhmudovich (Western European Studies, 2025)
This article explores the classification of competencies within the content of vocational education, emphasizing the importance of aligning educational outcomes with labor market demands. It outlines key distinctions between competency-based and traditional education, highlighting the role of knowledge, skills, and abilities in competency formation. Drawing on international practices and regulations, such as Uzbekistan's national framework for professional skills development, the article categorizes competencies into four types: general cultural, personal, general occupational, and occupation-specific. These classifications aim to create adaptable professionals capable of meeting modern workplace demands while contributing to societal and cultural development
Keywords: Competency-based education; vocational education; knowledge